INTERNATIONAL ORGANIZATIONS LECTURER NOTE - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The International Organizations are based on bilateral or multilateral relations of sovereign States. International Organizations are both regional and global in characters. In its regional character, it centralizes limited number of States, e.g. East African Community (EAC), with regional centralized structures. While in the global character, it centralizes most of the States in the world, e.g. UN Some International Organizations focuses their objectives on single issues, while others focus their objectives on a number of issues. International Organizations are either open to new members or consist of a closed system. On occasion, International Organizations are established for certain duration as specified in their respective characters, but more often, no time restriction is applied. In some older literatures, IOs tend to be sub-divided into political and apolitical (not interested or involved in politics) organizations. Apolitical organizations refer to military organizations such as NETO, while the other refers to organizations dealing with administrative and technical issues. The differentiation between political and technical IOs is not helpful. It makes more sense to differentiation between International Governmental Organizations (IGOs) for example, UN, NATO, IMF, and World Bank, with International Non Governmental Organizations (INGOs) such as Amnesty International, International Committee of the Red Cross (ICRC), World Health Organization (WHO).